(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Tax obligations optional to perform culture of formation fundamental economic and psychological the basics complex analysis to do dedicated to. In the article traditional​​ Allingham-Sandmo economic model and modern "fiscal psychology " and "tax "moral" concepts between​​ scientific debates research​​​​ within Uzbekistan​​ of the Republic of Kazakhstan for 2023-2025 tax reforms, particularly tax​ administration​​ digitization, hidden the economy reduction and optional compatibility encouragement​​ measures realistic statistic information​​ based on analysis The results of the study show that taxpayer behavior is directly related not only to the likelihood of penalties and inspections, but also to trust in the state, the fairness of the tax system, and social norms.